Xu Fuguan’s methodology for interpreting Chinese intellectual history - Sernelj, Tea (Asian studies, 2023)
The article examines the research methodology of Chinese intellectual history developed by the Modern Confucian Xu Fuguan ??? (1904–1982). His novel methodological approach differed significantly from the methodology advocated by Fu Sinian ??? (1896–1950), the founder of the Institute of History and Philology of Academia Sinica in 1928, who advocated a rigorous adoption of Western scientific methodology in historical research, based exclusively on a philological perspective. Fu Sinian’s methodological approach, however, prevailed among Chinese historians in mainland China in the first half of the 20th century and in Taiwan after 1949. Xu Fuguan was highly critical of such an approach, considering it inadequate and inappropriate because it did not allow for conceptual interpretations on the one hand, and disregarded the contextualization and historical development of concepts and meanings on the other. Xu’s methodology is based on the application of the hermeneutic circle, which Xu calls dynamic and structural holism from a comparative perspective. In his methodology, a method of seeking embodied experience (zhui tiyan de fangfa ??????) and intersubjectivenes (zhuti jianxing ????) play a crucial role as they enable actualization of and communication with ancient thinkers in present times. However, Xu’s methodological approaches are also strikingly similar to Gadamer’s method of the fusion of horizons and Schleiermacher’s hermeneutic circle, which begs the question whether his critique of Fu’s adoption of Western methods was not based upon hypocritical grounds.
Keywords: contextualization; dinamični in strukturni holizem; dynamic and structural holism; fusion of horizons; Gadamer; hermeneutic circle; hermenevtični krog; kontekstualizacija; methodology; metoda iskanja utelešene izkušnje; metodologija; the method of seeking embodied experience; Xu Fuguan; zlitje horizontov